2018
DOI: 10.1561/2600000017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Synthesis of Reset Control Systems

Abstract: This survey paper overviews a large core of research results produced by the authors in the past decade about reset controllers for linear and nonlinear plants. The corresponding feedback laws generalize classical dynamic controllers because of the interplay of mixed continuous/discrete dynamics. The obtained closed-loop system falls then within the category of hybrid dynamical systems, with the specific feature that the hybrid nature arises from the nature of the controller, rather than the nature of the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 80 publications
(161 reference statements)
0
6
0
2
Order By: Relevance
“…This feature makes the framework of [23] very appealing for the study of control and optimization techniques in VPPs, for which stability and robustness guarantees are desirable properties that are not easy to certify. Moreover, it has been shown that advanced hybrid controllers, such as reset control [245], [246], synergistic hybrid control [247], and switching control [248], can overcome fundamental transient and steady state limitations of traditional smooth linear controllers. The development and implementation of hybrid and nonsmooth controllers in VPPs offer exciting research opportunities to achieve performance levels that are unattainable via traditional techniques.…”
Section: C: Event-triggered Sampled-data and Hybrid Control In Vppsmentioning
confidence: 99%
“…This feature makes the framework of [23] very appealing for the study of control and optimization techniques in VPPs, for which stability and robustness guarantees are desirable properties that are not easy to certify. Moreover, it has been shown that advanced hybrid controllers, such as reset control [245], [246], synergistic hybrid control [247], and switching control [248], can overcome fundamental transient and steady state limitations of traditional smooth linear controllers. The development and implementation of hybrid and nonsmooth controllers in VPPs offer exciting research opportunities to achieve performance levels that are unattainable via traditional techniques.…”
Section: C: Event-triggered Sampled-data and Hybrid Control In Vppsmentioning
confidence: 99%
“…Example 4 (Clegg Integrator). The Clegg integrator connected to an integrating plant has been shown to overcome intrinsic limitations of linear feedback [4], (see also [29]). More specifically, using the εregularization suggested in [27], we focus on the hybrid closed-loop…”
Section: Stability Conditions Using L F (A C)mentioning
confidence: 99%
“…Ils ont été introduits dans les années 50 [5] dans l'idée d'exploiter la réinitialisation pour améliorer le comportement d'un système contrôlé avec un simple contrôleur linéaire [2], [16], [14]. Un récent tour d'horizon de cette classe de systèmes hybrides peut être trouvé dans [22].…”
Section: Introductionunclassified